Global spatio-temporal sampling characteristics of Moon-based Earth observations. Issue 20 (18th October 2021) - Deng, Yu; Guo, Huadong; Liu, Guang; Huang, Jing; Dong, Runbo; Wang, Hairong; Ye, Hanlin
ABSTRACT: A Moon-based platform can provide efficient observations of large-scale geoscience phenomena on Earth. This study focuses on the global spatio-temporal sampling characteristics of Moon-based Earth observations and quantifies the variations of the spatio-temporal sampling distributions to establish a suitable accumulated sampling period. A theoretical derivation is performed based on the parametric equations, while proposing a metric for measuring the uniformity of the spatio-temporal distributions. Results show that the distributions are mainly affected by the position of the nadir corresponding to the start time and the accumulated sampling period. We find that the accumulated spatio-temporal sampling presents a strong periodicity with one orbital period.